Pengaruh Model Pembelajaran Kooperatif Tipe Picture and Picture untuk Mengembangkan Kognitif melalui Kegiatan Sains pada Anak Usia Dini Kelompok B di TK Islam Minhajul Muslim - Devi, Shalsa Pramitha; Dedih Surana; Afrianti, Nurul (UNISBA Press, 2023)
Abstract. Cognitive ability problems (logical thinking) such as looking for differences, analyzing, solving problems, and recognizing cause and effect in material are also found in group B children in Minhajul Muslim Islamic Kindergarten Subang Reality shows that the ability is still known with children not understanding in observing a simple action in their environmentthis study aims to determine the cognitive development of group B children in Minhajul Muslim Islamic Kindergarten (logical thinking) in the model This research is a quasi-experimental quantitative research The research design used is randomized pre-test, post test control group design, data collection techniques used in testing, namely converting raw scores into z and t scores, conducting statistical tests, and hypothesis testing. The cognitive ability of group B children in Minhajul Muslim Subang Islamic Kindergarten after the application of the picture and picture type cooperative learning model showed an increase based on the results of the study showed that the average score of the pretest control group was 36.69 and the experimental group posttest was 41.19 meaning that there was an increase in children's logical thinking after getting the Picture and picture Type Cooperative Learning Model treatment. Thus, it can be concluded that the provision of Picture and Picture Type Cooperative Learning Model provides a significant improvement to the development of logical thinking in experimental group children. Based on the results of the researchers, the picture and picture type cooperative learning model is effective to become one of the models used in improving cognitive abilities (logical thinking). Abstrak. Permasalahan kemampuan kognitif (berfikir logis) seperti mencari perbedaan, menganalisa, memecahkan masalah, dan mengenal sebab-akibat dalam materi juga ditemukan pada anak kelompok B di TK Islam Minhajul Muslim Subang Realitas menunjukkan kemam puan masih diketahui dengan anak tidak mengerti dalam mengamati suatu tindakan sederhana yang ada di lingkungannya penelitian ini bertujuan untuk mengetahui perkembangan kognitif anak kelompok B di TK Islam Minhajul Muslim (berpikir logis) dalam model pembelajaran kooperatif tipe picture and picture penelitian ini merupakan penelitian kuantitatif quasi eksperimen desain penelitian yang digunakan adalah randomized pre-test, post test control group design, Teknik pengumpulan data yang digunakan dalam pengujian yaitu mengubah skor mentah ke dalam z dan t skor, melakukan uji statistik, dan pengujian hipotesis. Kemampuan kognitif anak kelompok B di TK Islam Minhajul Muslim subang setelah diterapkannya model pembelajaraan kooperatif tipe picture and picture menunjukkan ada nya peningkatan berdasarkan hasil penelitian menunjukkan bahwa nilai rata-rata kelompok kontrol pretest 36.69 dan posttest kelompok eksperimen 41.19 artinya terjadi peningkatan berpikir logis anak setelah mendapatkan perlakuan Model Pembelajaran Kooperatif Tipe Picture and picture. Dengan demikian, dapat disimpulkan bahwa pemberian Model Pembelajaran Kooperatif Tipe Picture and picture memberikan peningkatan secara signifikan terhadap perkembangan berpikir logis pada anak kelompok eksperimen. Berdasarkan hasil peneliti maka model pembelajaran kooperatif tipe picture and picture efektif untuk menjadi salah satu model yang digunakan dalam meningkatkan kemampuan kognitif (berpikir logis).